Outcomes of coronavirus disease 2019 in patients with neuromyelitis optica and associated disorders. (27th November 2020) - Louapre, Céline; Maillart, Elisabeth; Papeix, Caroline; Zeidan, Sinead; Biotti, Damien; Lepine, Zoé; Wahab, Abir; Zedet, Mickael; Labauge, Pierre; Tilikete, Caroline; Pique, Julie; Tourbah, Ayman; et al.
Abstract: Background: Outcomes of coronavirus disease 2019 (COVID‐19) in patients with neuromyelitis optica spectrum disorders (NMOSD) or myelin oligodendrocyte glycoprotein antibody‐associated disease (MOGAD), often treated with immunosuppressive therapies, are still unknown. Methods: We conducted a multicenter, retrospective, observational cohort study among all French expert centers for neuromyelitis optica and related disorders. Patients with NMOSD or MOGAD included in the study received a confirmed or highly suspected diagnosis of COVID‐19 between 1 March 2020 and 30 June 2020. Main outcome was COVID‐19 severity score assessed on a seven‐point ordinal scale ranging from 1 (not hospitalized with no limitations on activities) to 7 (death). Results: Fifteen cases (mean [SD] age: 39.3 [14.3] years, 11 female) were included. Five patients (33.3%) were hospitalized, all receiving rituximab. A 24‐year‐old patient with positive aquaporine‐4 antibody, with obesity as comorbidity, needed mechanical ventilation. Outpatients were receiving anti‐CD20 (5), mycophenolate mofetil (3) or azathioprine (3). They were younger (mean [SD] age: 37.0 [13.4] years), with a longer disease duration (mean [SD]: 8.3 [6.3] years) and had a lower expanded disability severity score (EDSS) score (median [range] EDSS: 2.5 [0–4]) relative to patients requiring hospitalization (mean [SD] age: 44.0 [16.4] years, mean [SD] disease duration: 5.8 [5.5] years, median [range] EDSS: 4 [0–6.5]). Conclusions: COVID‐19 outcome was overall favorable in this cohort. Larger international studies are needed to identify risk factors of severe COVID‐19; however, we recommend personal protective measures to reduce risk of SARS‐CoV‐2 infection in this immunocompromised population. Abstract : We present a cohort of 15 patients with neuromyelitis optica and associated disorders who had Coronavirus disease 2019 (COVID‐19). COVID‐19 outcome was overall favorable, 5 patients, all on Rituximab, needed hospitalization, and one patient needed mechanical ventilation.